Factors affecting work productivity of employees in the transportation department of East Kalimantan Province - Jubaidi Jubaidi; Dewi Laila Sari; Cindy Francisca Anastasia; Denisa Amelia; Bagus Falakhi Zuliansa (Institute of Computer Science (IOCS), 2024)
Productivity reflects the efficient way of using various resources to create products or services. Basically there are several factors that affect employee work productivity, one of which is communication skills, discipline, leadership patterns and work environment. The East Kalimantan Province Transportation Service really needs employees who have high productivity in improving services to the community in the transportation sector. The purpose of this research is to analyze the various variables that are used as factors that influence employee productivity at the East Kalimantan Provincial Transportation Service. The data analyzed came from questionnaires distributed to 80 employees. Data collection using saturated sample technique (population). Data analysis used multiple linear regression analysis through the SPSS 22 program. The results showed that simultaneously all independent variables had a significant effect on employee productivity while partially only training and leadership pattern variables had a significant effect on employee productivity while communication skills, work discipline, level of education and work environment partially had no significant effect on employee productivity